East Asia in action on arms assessing regional compliance to the UN POA on small arms and light weapons - Legaspi, Edgardo P.
East Asia in Action on Arms reviews the East Asian country reports on the implementation of the UN PoA four years after its adoption. Of the 12 countries considered for this study, only eight states have submitted one report each, while the other six governments have chosen to ignore the call of the UN to present to the international community what they have done to curb illicit trade in SALW. While some of the countries did try to come up with honest assessments on their situation and give an account of the measures they have come up with or plan to do in support of the PoA, the reports show obvious gaps in reporting, a tendency to focus on existing measures, and a seemingly lack of enthusiasm to go into new initiatives to control arms and the destruction it causes in people's lives. This study also looks beyond the country reports and asks: Are these efforts enough? Is the reporting process adequate? Does the UN PoA process--because it basically stems from a political agreement and not legally binding--allow for complacency? Do we need a stronger accord? Is East Asia in action or is there inaction on the problem of arms in the region?--Back cover